The therapeutic itinerary in mother-child healthcare: interfaces between culture and biomedicine - Rubia Fernanda Cardoso Amaral; Thayomara de Souza; Thayse Aparecida Palhano de Melo; Flávia Regina Souza Ramos (Universidade Federal do Ceará, 2012)
This study aimed to investigate the therapeutic itinerary in mother-child healthcare, while interfacing culture and biomedicine. With a qualitative approach and an exploratory design, this research was developed interviewing ten postpartum mothers in a district of Florianópolis/SC. Using the Atlas-Ti 5.0 software version, four categories emerged from the data: participants characterization; recognizing themselves as a part of the healthcare network; balancing knowledge and practices in the mother-child healthcare; culture and biomedicine - possible relations for a meaningful healthcare. The results have allowed to know the elements of the therapeutic itinerary of postnatal mothers in the healthcare of their children, especially in relations between the three subsystems which compose the healthcare system, in the health anthropology perspective. The mothers choose and define paths for the healthcare considering the particular case, including severity, availability and adequacy of resources, in a clear balance between knowledge, popular and scientific practices.